A Neural basis for Octanoic acid regulation of energy balance - Vanessa R. Haynes; Natalie J. Michael; Marco van den Top; Fei-Yue Zhao; Russell D. Brown; David De Souza; Garron T. Dodd; David Spanswick; Matthew J. Watt (Elsevier, 2020)
Objectives: Nutrient sensing by hypothalamic neurons is critical for the regulation of food intake and energy expenditure. We aimed to identify long- and medium-chain fatty acid species transported into the brain, their effects on energy balance, and the mechanisms by which they regulate activity of hypothalamic neurons. Methods: Simultaneous blood and cerebrospinal fluid (CSF) sampling was undertaken in rats and metabolic analyses using radiolabeled fatty acid tracers were performed on mice. Electrophysiological recording techniques were used to investigate signaling mechanisms underlying fatty acid-induced changes in activity of pro-opiomelanocortin (POMC) neurons. Results: Medium-chain fatty acid (MCFA) octanoic acid (C8:0), unlike long-chain fatty acids, was rapidly transported into the hypothalamus of mice and almost exclusively oxidized, causing rapid, transient reductions in food intake and increased energy expenditure. Octanoic acid differentially regulates the excitability of POMC neurons, activating these neurons directly via GPR40 and inducing inhibition via an indirect non-synaptic, purine, and adenosine receptor-dependent mechanism. Conclusions: MCFA octanoic acid is a central signaling nutrient that targets POMC neurons via distinct direct and indirect signal transduction pathways to instigate changes in energy status. These results could explain the beneficial health effects that accompany MCFA consumption. Keywords: Fatty acid metabolism, Pro-opiomelanocortin neuron, Food intake, Energy expenditure, Electrophysiology, Cerebrospinal fluid